Pengaruh Pemberian Pakan Yang Berbeda Terhadap Pertumbuhan Dan Sintasan Juvenil Udang Galah (Microbachiium Rosenbergii De Man) - Luh Saras Maheswari; Dewa Gede Semara Edi; I Made Kawan (Fakultas Pertanian, Universitas Warmadewa, 2022)
The gaff (macrobrachium rosenbergi DE man) is a type A highly cultivated freshwater shrimp that is kept in freshwater pools, lakes, and even in the ebb and flow of upstream and downstream. The stick shrimp has a larger size than other freshwater shrimps, which are relatively slow, so it takes a natural expert to increase growth and survive the natural food-fodder fodder worms that are used in Hong Kong worms and silk worms. The study is aimed at seeing how different types of feeding different types affect the growth and survival of the spear shrimps. This research was done in br. The full - time ministry of October 2020 to November 2020. The method used in this study is an experimental method with a full random design study (ral) With 5 (5) treatment and 3 (3) times deuteronomy. Analyze which Used in the study is a variable analysis (anova), and followed by UI BNT Studies have shown that there has been an effect of feeding on the growth and survival of the spear's prawn, an increase in absolute weight and absolute length Juvenile spear shrimp.